Relation of Emotional Intelligence, Self-esteem, Self-efficacy, and Psychological Well-Being Students of State Senior High School - Novi Rosita Rahmawati; Dany Moenindyah Handarini; Triyono Triyono (Pascasarjana UM, 2017)
Abstract: This study aims to know the relation of emotional intelligence (X1) and psychological well-being (Y), the relation of self-esteem (X2) and psychological well-being (Y), as well as the relation of self-efficacy (X3) and psychological well-being (Y) of public senior high school in the entire Malang city. This study was a non-experimental study with causal relationship study plan. The result of this research showed that there was a positive significant correlation between X1 and Y, X2 and Y, X3 and Y; X1, X2, X3 had strong linear relation with Y; the influence of the three independent variables was 50.7%, while the rest was influenced by other variables; X2 was the most influencing variable towards Y, the second was X1, and the last was X3.Key Words: Emotional Intelligence, Self-esteem, Self-efficacy, Psychological Well Being, Senior High School Students Abstrak: Penelitian ini bertujuan untuk mengetahui hubungan kecerdasan emosi (X1) dan psychological well being (Y) , self esteem (X2) dan psychological well being (Y), self efficacy (X3) dan psychological well being (Y) siswa SMA Negeri se-kota Malang. Pendekatan yang digunakan adalah non experimental research dengan jenis penelitian causal relationship study. Hasil penelitian menunjukkan ada hubungan positif signifikan antara X1 dan Y, X2 dan Y, X3 dan Y; X1, X2, X3 memiliki hubungan linear yang kuat dengan Y; pengaruh ketiga variabel independen sebesar 50,7%, sedangkan sisanya dipengaruhi oleh variabel lain; X2 vaktor yang berpengaruh terhadap Y, urutan kedua X1, dan urutan terakhir adalah X3.Kata kunci: Kecerdasan Emosi, Self esteem, Self Efficacy, Psychological Well Being, Siswa SMA